Nutritional intervention in interface to the development of Type 2 Diabetes Mellitus: the contribution of ultra-processed foods in the development of the pathology (Research, Society and Development, 2021)
The occurrence of Diabetes mellitus in a population group is mainly linked to socioeconomic and cultural factors, such as: urbanization, eating habits, sedentary lifestyle, stress, and also known family predisposition. Nutritional care in diabetes mellitus (DM) is one of the most challenging parts of treatment and lifestyle change strategies. The relevance of nutritional therapy in the treatment of DM has been emphasized since its discovery, as well as its challenging role in preventing, managing the disease and preventing the development of resulting complications. In view of such considerations, the present bibliographical research aims to identify the eating habits that favor the emergence of type 2 diabetes mellitus, for this, the nutritional aspects of diabetes were described; and epidemiological data so that he could establish the relationship between poor diet and the onset of type 2 diabetes. In the end, it was found that foods that are inadequate for consumption by diabetics have exaggerated amounts of sodium, fat, concentrated sugar, canned foods, and industrialized products with a high content of preservatives, in this sense it is ideal for people with diabetes to acquire healthy eating habits to avoid the acute and chronic complications of the disease.